[FeIII(salophene)Cl], a potent iron salophene complex overcomes multiple drug resistance in lymphoma and leukemia cells - Lee, Soo-Young; Hille, Annegret; Kitanovic, Igor; Jesse, Patrick; Henze, Günter; Wölfl, Stefan; Gust, Ronald; Prokop, Aram (Leukemia research, 2011)
We demonstrate the cytotoxic potential of the Schiff base iron complex [FeIII(salophene)Cl] in vitro and ex vivo and illustrate its ability to overcome multiple drug resistance in vincristine and daunorubicine resistant leukemic cells (Nalm-6). Treatment of lymphoma cells (BJAB) with [FeIII(salophene)Cl] led to the exclusion of unspecific necrosis, a concentration-dependent inhibition of proliferation and a specific apoptotic cell death. We further detected a significant loss of the mitochondrial membrane potential in lymphoma cells and an up- and downregulation of various apoptosis relevant genes, respectively, indicating the involvement of the intrinsic mitochondrial pathway.